Generating buy-in : mastering the language of leadership - Walton, Mark S., 1950- (American Management Association, 2004)
Crafting a strategic story that projects a positive future to your audience; speaking the language of buy-in with images that mold powerful thoughts and emotions in your listeners; and putting the language to work in service of your goal - whether the goal is to raise sales, inspire a work force, or win a Presidential election."--Jacket